The influence of service quality on customer loyalty mediated by customer satisfaction (Study at PT WOM Finance Medan Branch 1) - Wahyudin, Arif; Saparso, Saparso (Enrichment : Journal of Management, 2025)
This research examines the influence of service quality and customer satisfaction on customer loyalty at PT. WOM Finance Medan 1, with customer satisfaction positioned as a mediating variable. The study is motivated by the company’s ongoing challenge to maintain customer retention amidst increasingly competitive conditions in the financing industry. Employing a quantitative research design, data were collected through a survey of 85 respondents and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS version 4. The results reveal that: (1) service quality has a significant positive effect on customer loyalty (t-statistic = 2.780, p-value = 0.005); (2) customer satisfaction significantly influences customer loyalty (t-statistic = 4.757, p-value = 0.000); (3) service quality exerts a significant positive impact on customer satisfaction (t-statistic = 15.443, p-value = 0.000); and (4) service quality, when mediated by customer satisfaction, does not significantly affect customer loyalty (t-statistic = 1.702, p-value = 0.089). These findings underscore the critical role of consistently enhancing service quality as a strategic driver of customer satisfaction and loyalty. The study offers practical insights for PT. WOM Finance and similar financial institutions in developing effective service improvement strategies to strengthen long-term customer relationships and competitive advantage. For PT. WOM Finance Tangerang Branch, the results of this study indicate the need to focus on improving aspects of service quality that directly affect customer loyalty. Based on the research results, PT. WOM Finance Tangerang Branch needs to prioritize improving service quality because it has been proven to have a significant influence on customer loyalty, both directly and through customer satisfaction. Improving service quality can be done by providing consistent, friendly, and responsive service to build long-term relationships with customers.